Derosion Lattice Performance and Optimization in Solving an End Effect Assessed by CFD: A Case Study in Thailands Beach - Jatuporn Thongsri; Worapol Tangsopa; Mongkol Kaewbumrung; Mongkol Phanak; Wutthikrai Busayaporn (My University, 2022)
Thailand’s beach had a severe coastal erosion problem at the end of rock dams called the “end effect”. One of the innovative solutions to solve this problem is to use the derosion lattice (DL). However, since the DL performance depends on installing conditions such as angle of attack, placement position, terrain, and climate, computational fluid dynamics (CFD) was applied to assess the end effect’s occurrence and optimize the performance of DL’s installation. Based on Khao Rup Chang’s condition, a suffered beach in Thailand was used as a case study, and a free surface flow simulation was performed in the transient state using ANSYS Fluent, a CFD software, which revealed water waves flow through the beach with and without the DL installation cases. Furthermore, the CFD-assessed results indicated that the angle of attack and placement position affected the DL performance as expected. In optimization, the 15° angle of attack with the DL placement adjacent to the rock dam was the proper condition. After being applied at the actual site, the DL can help reduce erosion, increase sedimentation, and solve the end effect with excellent performance.
Keywords: Installation; Flow conditions; Hydraulic flow and structures